Copper stress‐induced changes in leaf soluble proteome of Cu‐sensitive and tolerant Agrostis capillaris L. populations. Issue 9 (May 2016) - Hego, Elena; Vilain, Sébastien; Barré, Aurélien; Claverol, Stéphane; Dupuy, Jean‐William; Lalanne, Céline; Bonneu, Marc; Plomion, Christophe; Mench, Michel
Abstract : Changes in leaf soluble proteome were explored in 3‐month‐old plants of metallicolous (M) and nonmetallicolous (NM) Agrostis capillaris L. populations exposed to increasing Cu concentrations (1–50 μM) to investigate molecular mechanisms underlying plant responses to Cu excess and tolerance of M plants. Plants were cultivated on perlite (CuSO4 spiked‐nutrient solution). Soluble proteins, extracted by the trichloroacetic acid/acetone procedure, were separated with 2‐DE (linear 4–7 pH gradient). Analysis of CCB‐stained gels (PDQuest) reproducibly detected 214 spots, and 64 proteins differentially expressed were identified using LC‐MS/MS. In both populations, Cu excess impacted both light‐dependent (OEE, cytochrome b6‐f complex, and chlorophyll a‐b binding protein), and ‐independent (RuBisCO) photosynthesis reactions, more intensively in NM leaves (ferredoxin‐NADP reductase and metalloprotease FTSH2). In both populations, upregulation of isocitrate dehydrogenase and cysteine/methionine synthases respectively suggested increased isocitrate oxidation and enhanced need for S‐containing amino‐acids, likely for chelation and detoxification. In NM leaves, an increasing need for energetic compounds was indicated by the stimulation of ATPases, glycolysis, pentose phosphate pathway, and Calvin cycle enzymes; impacts on protein metabolism and oxidative stress increase were respectively suggested by the rise of chaperones and redox enzymes. Overexpression of a HSP70 may be pivotal for M Cu tolerance by protecting protein metabolism. All MS data have been deposited in the ProteomeXchange with the dataset identifier PXD001930 (http//proteomecentral.proteomexchange.org/dataset/PXD001930 ).